Bakawan - Untalan, Catherine Yu; Sarmiento, Reena Rae de Leon; Tobias, Mae Astrid; Bascon, Van Zeus Allen; Camacho, Eli (Quezon City Adarna House, Inc., 2009)
A modern fable of animals living in a mangrove that suddenly have to deal with pollution.
Keywords: Children's stories, Philippine (English); Mangrove animals -- Juvenile literature; Mangrove conservation -- Juvenile literature